Depolarization in Delivering Public Services? Impacts of Minimum Service Standards (MSS) on the Quality of Health Services in Indonesia - Mohammad Roudo; Tengku Munawar Chalil (Journal of Regional and City Planning, 2016)
Abstract. Some scholars argue that decentralization policy tends to create polarization, i.e. an increase of inequality/disparity among districts. To deal with this problem, Minimum Service Standards (MSS) were introduced as a key strategy in decentralizing Indonesia. In this research, we tried to find out through MSS performance measurements whether imposing standards can be effective in a decentralized system by seeking its impacts on polarization/depolarization in the delivery of public services, specifically in the health sector. This question is basically a response to the common criticism that decentralization is good to create equality between central government and local governments but often does not work to achieve equality among local governments. Using self-assessment data from a sample of 54 districts from 534 districts in Indonesia, from 2010 to 2013, we found that the existence of depolarization in the delivery of public services could potentially occur among regions by reducing the gap between their public service performance and the targets of MSS. We acknowledge that there are weaknesses in the validity of the self-assessment data, caused by a lack of knowledge and skills to execute the self-assessment according to the official guidelines, by the overrating of target achievements, as well as the lack of data from independent sources to confirm the self-assessment outcomes. We also acknowledge that differences in financial capacity are still the main determinant why one district is more successful in achieving the MSS targets compared to other districts. Keywords. Decentralization, Public Service, Minimum Standard Service